On the calculation of second-order magnetic properties using subsystem approaches in a relativistic framework. Issue 12 (10th March 2017) - Olejniczak, Małgorzata; Bast, Radovan; Pereira Gomes, André Severo
Abstract : The implementation of second-order magnetic properties in a frozen density embedding scheme in a four component relativistic framework is outlined and applied to model H2 X–H2 O systems (X = Se, Te, Po). Abstract : We report an implementation of nuclear magnetic resonance (NMR) shielding ( σ ), isotope-independent indirect spin–spin coupling ( K ) and the magnetizability ( ξ ) tensors in a frozen density embedding scheme using the four-component (4c) relativistic Dirac–Coulomb (DC) Hamiltonian and non-collinear spin density functional theory. The formalism takes into account the magnetic balance between the large and the small components of molecular spinors and assures the gauge-origin independence of the NMR shielding and magnetizability results. This implementation has been applied to hydrogen-bonded HXH⋯OH2 complexes (X = Se, Te, Po) and compared with supermolecular calculations and with an approach based on the integration of the magnetically induced current density vector. A comparison with the approximate zeroth-order regular approximation (ZORA) Hamiltonian indicates non-negligible differences in σ and K in the HPoH⋯OH2 complex, and calls for a thorough comparison of ZORA and DC Hamiltonians in the description of environment effects on NMR parameters for molecular systems with heavy elements.